Yield quality of Setaria italica accessions originated from Numfor Island, Papua, Indonesia - SYUKUR KARAMANG; ARIFFIN ARIFFIN; EKO WIDARYANTO; NURUL AINI (Society for Indonesian Biodiversity, 2023)
Abstract. Karamang S, Ariffin, Widaryanto E, Aini N. 2023. Yield quality of Setaria italica accessions originated from Numfor Island, Papua, Indonesia. Biodiversitas 24: 1878-1885. Pokem (Setaria italica L. Beauv) is among the various germplasms of food plant diversity in Papua, especially in Numfor Island along with its traditional cultivation. Huge attention is needed in sustaining plant development due to its high nutritional value. Therefore, the study aims to (i) search for S. italica accessions with the highest yields and nutrient content in ex-situ cultivation, and (ii) S. italica gain accessions from the island of Numfor which contains phytochemical and antioxidant activity compounds. This study was carried out at the Experimental Garden of the Faculty of Agriculture, the University of Papua in Amban Manokwari. The plant materials used were 15 accessions of S. italica grains derived from existing cultivated locations of Numfor Island, Papua. The experiment was carried out using Randomized Block Design (RBD) with 4 replications. Yield component characters, nutritional content, total flavonoid and phenolic content, as well as antioxidant activity were observed. The results revealed that accession Sub Manggunsi 3 (SM3) had the highest grain yield. Based on nutrient contents, the highest recorded by Namber 2 (NM 2) accession for carbohydrate content, followed by Sub Manggunsi 2/SM2 (raw fiber), Kansai 3/KN3 and Sub Manggunsi 3/SM3 (protein content), Sub Manggunsi 1/SM1 (water content), Kameri 3/KM3 and Rimba Raya2/RR2 (fat content), Namber 3/NM3 (ash content); while Kameri 1 (KM1) accession, Rimba Raya 2 (RR2) and Kansai 1 (KM3) accession performed high content of total flavonoid, total phenol and antioxidant activity.